The doctrine of corporate social responsibility: towards binding legal responsibility - Eishan Jan, Mohammad Naqib; Lawan Haruna, Abdulrashid (Lexis Nexis Malaysia Sdn Bhd, 2016)
Corporate social responsibility (CSR) is an all-encompassing phenomenon that recently draws the attention of many practitioners from business communities, environmental activists, human rights advocates and the international community. Corporations are business enterprises that are established with the main aim of providing profitable dividend to the shareholders at the end of every business year. However, profit maximization should not be the sole aim of a business enterprise, as such CSR attaches certain voluntary social responsibility on corporations. This stems from the increasing vital role of corporations in the political, social and economic spheres of human endeavors. Accordingly, CSR requires corporations to discharge certain social responsibility that enhances the welfare of the community and environment in which they operate. The paper examines the nexus that exists between CSR and other concepts such as sustainable development, corporate governance and social contract. It discusses CSR as a voluntary action to be taken by corporations though it has gradually started enjoying the flavor of law. The paper further argues that CSR has for long been under the influence of law and there are certain principles of law such as ‘legal personality’ and ‘neighbor principle’, which can be essential in providing legal framework for CSR. It is suggested that in certain cases there is need for a binding legislation to impose obligation and control over corporations in terms of CSR activities to be engaged in by the corporations.